Rational synthesis of gold-ceria catalysts supported on reduced graphene oxide with remarkable activity for CO oxidation - Abdallah F Zedan; Sherif Moussa; M Samy El-Shall (Materials Research Express, 2023)
Gold (Au)- and ceria (CeO _2 )-based catalysts are amongst the most active catalysts for the gas phase CO oxidation reaction. Nevertheless, nanosized Au and CeO _2 catalysts may encounter heat-induced sintering in thermochemical catalytic reactions. Herein, we report on the rational one-pot synthesis of ceria-reduced graphene oxide (CeO _2 -RGO) using a facile ethylenediamine (EDA)-assisted solvothermal method. Standalone RGO and free-standing CeO _2 were also prepared using the same EDA-assisted method for comparison. We then incorporated Au into the prepared samples by colloidal reduction and evaluated the catalytic activity of the different catalysts for CO oxidation. The RGO-supported CeO _2 surpassed the free-standing CeO _2 , exhibiting a 100% CO conversion at 285 °C compared to 340 °C in the case of CeO _2 . Interestingly, the RGO-supported Au/CeO _2 catalysts outperformed the Au/CeO _2 catalysts and achieved a 100% CO conversion at 76 °C compared to 113 °C in the case of Au/CeO _2 . Additionally, the Au/CeO _2 -RGO catalyst demonstrated remarkable room-temperature activity with simultaneous 72% CO conversion. This outstanding performance was attributed to the unique dispersion and size characteristics of the RGO-supported CeO _2 and Au catalysts in the ternary Au/CeO _2 -RGO nanocomposite, as revealed by TEM and XPS, among other techniques.